Molecular Characterization of Bacteria, Detection of Enterotoxin Genes, and Screening of Antibiotic Susceptibility Patterns in Traditionally Processed Meat Products of Sikkim, India - Bhutia, Meera Ongmu; Thapa, Namrata; Tamang, Jyoti Prakash (Frontiers in Microbiology, 2021)
Abstract Lesser-known traditionally processed meat products such as beef kargyong, pork kargyong, satchu and khyopeh are popular food items in the Himalayan state of Sikkim in India. The present study aimed to assess the microbiological safety of traditional meat products by identifying the potential spoilage or pathogenic bacteria, detecting the enterotoxins, and screening the antibiotic susceptibility patterns. The pH and moisture contents of meat products varied from 5.3-5.9 and 1.5-18%, respectively. The microbial loads of aerobic bacteria were 105 to 107 cfu/g, Staphylococcus 103 to 106 cfu/g, Bacillus 104 to 106 cfu/g and total coliform 102 to 107 cfu/g, respectively. Based on 16S rRNA gene sequencing, bacterial species isolated from traditionally processed meat products were Staphylococcus piscifermentans, Citrobacter freundii, Enterococcus faecalis, Salmonella enterica, Staphylococcus aureus, Citrobacter werkamanii, Klebsiella pneumonia, Macrococcus caseolyticus, Klebsiella aerogenes, Staphylococcus saprophyticus, Pseudocitrobacter anthropi, Citrobacter europaeus, Shigella sonnei, Escherichia fergusonii, Klebsiella grimontii, Burkholderia cepacia and Bacillus cereus. The ELISA tests detected Salmonella spp. and enterotoxins produced by Bacillus cereus well as Staphylococcus in a few tested samples. However, the PCR method did not detect the virulence genes of Bacillus cereus and Salmonella in the isolates. Virulence gene (sea) was detected in Staphylococcus piscifermentans BSLST44 and Staphylococcus piscifermentans BULST54 isolated from beef kargyong and Staphylococcus aureus PSST53 isolated from pork kargyong. No enterotoxins were detected in khyopeh samples. The antibiotic sensitivity test showed all bacterial strains were susceptible towards gentamicin, cotrimoxazole, norfloxacin, and trimethoprim. Gram-positive bacteria showed 100% sensitivity against clindamycin and erythromycin, however, 50% of the resistance pattern was observed against oxacillin followed by penicillin (33%) and ampicillin (27%).